(Development of Local Food Snack Repository Application to Increase the Creativity of Mothers in Family Menu Provision) - Sri Yunanci Gobel; Kasmawati Kasmawati; Masrif Masrif; Lydia Fanny; Suci Desiani S; Cicilia Tri Sakty (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
Local food snack recipes that will be data in this repository application have been grouped based on keywords or food ingredients that are input into the application. This application is designed using (FrontEnd) Flutter and data processing (BackEnd) API CI4 and the application is run in an android-based smartphone environment. With this Android-based food recipe repository application, users can search for food recipe data based on the region of origin, keywords or food ingredients inputted into the application. The application will also carry out the process of selecting food ingredient data that is close to the type of food recipe that exists, using several selection methods / algorithms that have been made. The use of this application is expected to be able to provide inspiration for mothers in preparing and providing healthy and nutritious food for the family, especially for children from the womb to child development.